Biophysical Consequences of a Relaxing Beaufort Gyre. Issue 2 (17th January 2020) - Zhang, Jinlun; Spitz, Yvette H.; Steele, Michael; Ashjian, Carin; Campbell, Robert; Schweiger, Axel
Abstract: A biophysical model shows that Beaufort Gyre (BG) intensification in 2004–2016 is followed by relaxation in 2017–2018, based on a BG variability index. BG intensification leads to enhanced downwelling in the central Canada Basin (CCB) and upwelling along the coast. In the CCB, enhanced downwelling reduces nutrients, thus lowering primary productivity (PP) and plankton biomass. Enhanced upwelling along the coast and in parts of the Chukchi shelf/slope increases nutrients, leading to elevated PP/biomass in the Pacific Arctic Ocean (PAO) outside of the CCB. The overall PAO PP/biomass is dominated by the shelf/slope response and thus increases during BG intensification. As the BG relaxes in 2017–2018, these processes largely reverse, with increasing PP/biomass in the CCB and decreasing PP/biomass in most of the shelf/slope regions. Because the shelf/slope regions are much more productive than the CCB, BG relaxation has the tendency to reduce the overall production in the PAO. Key Points: An index indicates Beaufort Gyre relaxation in 2017–2018, with reduced Canada Basin downwelling and coastal upwelling Beaufort Gyre intensification (relaxation) leads to lower (higher) plankton biomass in Canada Basin and higher (lower) biomass in shelves Overall primary productivity in the Pacific Arctic increases (decreases) with Beaufort Gyre intensification (relaxation)